A preliminary cross-cultural study of Hikikomori and Internet Gaming Disorder: The moderating effects of game-playing time and living with parents. (June 2019) - Stavropoulos, Vasileios; Anderson, Emma Ela; Beard, Charlotte; Latifi, Mohammed Qasim; Kuss, Daria; Griffiths, Mark
Abstract: Background: Internet Gaming Disorder (IGD) and Hikikomori (an extreme form of social real-life withdrawal, where individuals isolate themselves from society) have both been suggested as mental disorders that require further clinical research, particularly among young adult populations. Objective: To add to the extant literature, the present study used a cross-cultural, cross-sectional design to investigate the association between Hikikomori and IGD, and the potential moderating effects of reported game-playing time and living with parents. Method: Two online samples of 153 Australian and 457 U.S.-North American young adult players of Massively Multiplayer Online (MMO) games were collected. The nine-item Internet Gaming Disorder Scale-Short Form (IGDS-SF9), and the Hikikomori Social Withdrawal Scale were administered to dimensionally assess IGD and Hikikomori, respectively. Results: Linear regression analyses confirmed that Hikikomori symptoms are associated with IGD. Additionally, moderation analyses indicated that the association was exacerbated by longer game playing time across both populations. Gamers living with their parents was a significant moderator of the relationship for the Australian sample. Conclusions: Extreme real-life social withdrawal and IGD are related, and this association is exacerbated for those who spend more time playing MMOs per day, and, for Australian participants, living with their parents. Highlights: Internet Gaming Disorder (IGD) and Hikikomori are two relatively new disorders. Hikikomori symptoms are associated with higher IGD scores. Longer periods of gaming exacerbated the Hikikomori-IGD association. Living with parents exacerbated IGD among Australian gamers.